Religious pluralism in Islamic law Dhimmis and others in the empire of law - Emon, Anver M. (Oxford : Oxford University Press, 2012)
Analysing the rules governing the treatment of foreigners in Islam and situating them in their historical, political, and legal context, this book sets out a framework for understanding these rules as part of a wider problem of governing through law amidst pluralism.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Dhimmis (Islamic law); Religious pluralism -- Islam